Dinamika Gaya Belajar Siswa Pada Budaya Boarding School Sekolah Menengah Atas Darul Arqam Garut - Ahmad Rifqy Ash-Shiddiqy (ISLAMICA, 2016)
Learning is a cultural activity, and in Islam, learning is an activity of worship. As a cultural activity, diversity in culture (multicultural) will generate diversity in learning styles; and as a religious activity, the learning activities are driven by faith. Understand the influence of cultural diversity (multiculturalism) is referred to as the power IV in Psychology (Pedersen, 1991), and the power of spiritualism has been widely referred to as the power of V in Psychology, to enhance the three previous strength: schools of Psychodynamic (strength I), sect Behavioristik (strength II ), and schools of Humanistic (strength III), in explaining human behavior. The influence of these two forces advanced towards attractive GB studied further in order to develop GB each individual optimally. Studies following successively discuss: (1) the conceptual framework GB, (2) the identification of issues and related phenomena, (3) research methods, (4) the results of the analysis, and (5) the implications for education and guidance and counseling , Research shows that students who learned by using learning styles (GB) they achieve higher performance than those who did not use (Dunn and Griggs, 1998: 13; Adi W. Gunawan, 2007: 139), because they learn through "options" GB they enjoy. Therefore, GB has been recognized had the "power" (Sullivan in Dunn and Griggs, 1998: 13), and pulled again that GB influenced by the culture and beliefs of each, as well as the leadership factor.